Teaching at a Minimum: Exploring the Wellbeing of Filipino Tertiary Educators who Quiet Quit - Varias, April Chanel Soriano; Conway, Gail (UIN Maulana Malik Ibrahim Malang, 2024)
The phenomenon of quiet quitting has gained traction in recent years across various professions, yet its impact on teachers remains underexplored particularly in the Philippines where teachers underpaid, unrecognized, and overworked. Therefore, this Generic Qualitative Inquiry study examined five male and female tertiary private school teachers who engage in quiet quitting behavior and how it impacts their well-being. Analyzed using VSAIEEDC model, emergent themes indicate that participants who quiet quit have grievances about school management, workload, and other people they encounter at school. Due to their perceptions of unfair treatment and excessive workload, participants quiet quit by sacrificing their teaching quality, meeting only the minimum requirements of their teaching position, retaliating against school injustice, and languishing at work. Quiet quitting leads to remorse and worries about teaching competency, which harms participants. Despite the negative impact of quiet quitting, participants express that it also reduces work stress. Maslach's Burnout, Self-determination, and Equity Theories explain findings. The paper also discusses teacher and school management implications and recommendations. KEY WORDS: domestic violence; income level; spousal communication